2021
DOI: 10.3390/antiox11010101
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Dermo-Cosmetic Evaluation of Cymbidium sp. (Orchidaceae) Cultivation By-Products

Abstract: Cymbidium is one of the most popular genera in Orchidaceae family, commercialized either as loose flowers or as potted plants in floriculture worldwide. The non-marketable parts are typically discarded (e.g., unsuitable flowers, leaves, pseudobulbs, roots), generating an enormous quantity of unutilized biomass. The above by-products were studied through phytochemical analysis and investigated for their dermo-cosmetic potential. The initial antioxidant, anti-tyrosinase, anti-elastase, and anti-collagenase assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The new compounds 14 and 15 as well as oleocanthal (6), oleacein (7), oleocanthalic (8) and oleaceinic acids (9) were tested for their ability to interact with 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid (ABTS), stable free radicals useful for investigating the free radical scavenging activity. These assays were performed according to previously described methods, with slight modifications [19,20]. The scavenging activity is expressed in IC 50 values (concentration required for 50 % inhibition of the corresponding reagent) (▶ Table 2, entries I and II).…”
Section: Resultsmentioning
confidence: 99%
“…The new compounds 14 and 15 as well as oleocanthal (6), oleacein (7), oleocanthalic (8) and oleaceinic acids (9) were tested for their ability to interact with 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid (ABTS), stable free radicals useful for investigating the free radical scavenging activity. These assays were performed according to previously described methods, with slight modifications [19,20]. The scavenging activity is expressed in IC 50 values (concentration required for 50 % inhibition of the corresponding reagent) (▶ Table 2, entries I and II).…”
Section: Resultsmentioning
confidence: 99%
“…Axiotis et al studied the antityrosinase, antioxidant, and collagenase inhibitory activities of all the Cymbidium sp. byproduct extracts . From the results obtained, the pseudobulbs’ ethanol/water extract presented the highest antityrosinase activity among other extracts, showing 64.11 ± 2.34% inhibition at 300 μg/mL.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…However, the dichloromethane (DCM) and ethanol/water extracts of pseudobulbs (IC 50 = 165.78 and 233.32 μg/mL, respectively) and roots (IC 50 = 174.61 and 304.02 μg/mL, respectively) showed weak antioxidant activity. Regarding the collagenase inhibitory test, ethyl acetate extracts of pseudobulbs and roots exhibited high inhibitory activity by displaying 4.01 ± 1.32% and 82.79 ± 1.60% inhibition of collagenase at 75 μg/mL …”
Section: Biological Activitiesmentioning
confidence: 99%
“…Orchids have been used all over the world in traditional healing and treatment systems for various diseases, such as chest pain, arthritis, syphilis, jaundice, cholera, acidity, eczema, tumor, piles, tuberculosis, wounds, stomach disorders, boils, inflammation, menstrual disorders, spermatorrhea, leucoderma, slantendicular, muscular pain, earache, sexually transmitted diseases, blood dysentery, hepatitis, bone fractures, rheumatism, asthma, malaria, paralysis, and dyspepsia (Kong et al, 2003;Pant, 2013;Rahman et al, 2022). It is suggested that the pharmaceutical properties of orchids are due to the activities of many phytochemicals, including alkaloids, bibenzyl derivatives, flavonoids, carotenoids, phenanthrenes, phenanthropyrans, stilbenes, anthocyanins, glycosides, sterols, and terpenoids, which are present in various parts of orchid plants (Zhang et al, 2015;Axiotis et al, 2021). In recent years, the assessment of the anti-diabetic, anti-inflammatory, and antioxidant properties of orchids has received considerable attention Warinhomhoun et al, 2021;Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%